2016
DOI: 10.1371/journal.ppat.1005801
|View full text |Cite|
|
Sign up to set email alerts
|

KSHV-Mediated Regulation of Par3 and SNAIL Contributes to B-Cell Proliferation

Abstract: Studies have suggested that Epithelial–Mesenchymal Transition (EMT) and transformation is an important step in progression to cancer. Par3 (partitioning-defective protein) is a crucial factor in regulating epithelial cell polarity. However, the mechanism by which the latency associated nuclear antigen (LANA) encoded by Kaposi's Sarcoma associated herpesvirus (KSHV) regulates Par3 and EMTs markers (Epithelial-Mesenchymal Transition) during viral-mediated B-cell oncogenesis has not been fully explored. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 85 publications
(123 reference statements)
0
20
0
Order By: Relevance
“…(H) Using the standard trypan blue exclusion assay method, proliferation of GC cells under different conditions was scored. (I) A colony formation assay was performed using a previously described method ( 68 ) and crystal violet staining. (J) A model depicting the modulation of the cell cycle, apoptosis, and DNA damage repair pathways that can lead to tumorigenesis of EBV- H. pylori -positive gastric epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(H) Using the standard trypan blue exclusion assay method, proliferation of GC cells under different conditions was scored. (I) A colony formation assay was performed using a previously described method ( 68 ) and crystal violet staining. (J) A model depicting the modulation of the cell cycle, apoptosis, and DNA damage repair pathways that can lead to tumorigenesis of EBV- H. pylori -positive gastric epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…A cell proliferation assay was performed using trypan blue exclusion and crystal violet staining methods as previously described ( 67 , 68 ). Brief descriptions are provided in Text S1 and elsewhere in Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…However, Snail-overexpressing cells can respond to mitogenic signals by transiently decreasing p21 expression, which favors the transition to S phase (43). The study also reported that Snail repressed p21 expression in infected B cells contributing to KSHV induced B-cell oncogenesis (44). Snail knockdown was reported to led to the upregulation of p21 and downregulation of Cdc2, causing a decrease of G 1 and S periods and an increase of the G 2 -M population (45).…”
Section: Discussionmentioning
confidence: 90%
“…In Epstein-Barr virus (EBV)-transformed B cells, expression of miR-200 RNAs, which directly induces MET in cancer models (30), causes a switch from latency to lytic replication (31). Similarly, during Kaposi's sarcoma-associated herpesvirus (KSHV) infection of B cells, the latency-associated nuclear antigen (LANA) induces mesenchymal features by up-regulating SNAIL (32). Suppression of LANA breaks latency (33), inhibits SNAIL, and induces epithelial genes including CDH1 (32), features consistent with MET.…”
Section: Biogenic Amine Gpcr Potassium Channel and Amino Acid Transpmentioning
confidence: 99%